Comparison of battery electric vehicle and hybrid electric vehicle - Hladchenko, D. V.; Beshta, O. S. (My University, 2023)
The topic of electric vehicles is popular nowadays, as electric vehicles, during their exploitation, leave less emission compared to internal combustion engine vehicles. Thus, according to [1], if in 2020, electric vehicle sales were only 4%, in 2022, this value has skyrocketed to 14%, .The term “electric vehicle” (EV) generally refers to a vehicle that is driven by an electric motor powered by a self-contained power source. In this article we will discuss about two varieties of electric vehicles: Battery EV (BEV) and Plug-In Hybrid EV (PHEV). Look at their positive and negative sides, from the point of view of an ordinary user and make a definite conclusion on this basis.
Keywords: electric vehicle; електромобіль; Plug-in Hybrid Electric Vehicle; Battery Electric Vehicle; акумуляторний електромобіль